2020
DOI: 10.1007/s00394-020-02363-5
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of Hayward green kiwifruit on dietary protein digestion and protein metabolism

Abstract: Purpose The purpose of the study was to determine if an actinidin protease aids gastric digestion and the protein anabolic response to dietary protein. Methods Hayward green kiwifruit (containing an actinidin protease) and Hort 16A gold kiwifruit (devoid of actinidin protease) were given in conjunction with a beef meal to healthy older subjects. Twelve healthy older males (N = 6) and females (N = 6) were studied with a randomized, double-blinded, crossover design to assess muscle and whole-body protein metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Blood and muscle samples were analyzed for isotope enrichment using methods previously described (Park et al, 2021 ). Briefly, upon thawing, biopsy samples were precipitated with 800 µl of 14% perchloroacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Blood and muscle samples were analyzed for isotope enrichment using methods previously described (Park et al, 2021 ). Briefly, upon thawing, biopsy samples were precipitated with 800 µl of 14% perchloroacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in rates of polymer synthesis such as protein [ 26 , 58 ], DNA [ 59 , 60 ], RNA [ 59 , 61 ], triacylglycerol [ 62 , 63 ], and glucose (e.g., GNG) [ 64 , 65 ], from their respective precursors have clinical implications [ 66 , 67 ]. In this regard, the tracer incorporation model has been widely used to obtain the polymer synthesis rate and is predicated on the rate of tracer precursor incorporation to product for a given time period, yielding the fractional synthesis rate (FSR), which refers to the percent of the pool size that has been newly synthesized from the precursor for the most recent defined time period (%/time) [ 68 ].…”
Section: Basic Principles Of Stable Isotope Tracer Methodologymentioning
confidence: 99%
“…Contrary to protein food sources, dietary EAAs do not require digestion before appearing in the circulation, thus inducing rapid and complete appearance rates of EAAs in the circulation. Previous studies have shown that the rate of plasma EAA appearance varies depending on amino acid sources [39][40][41], and the speed of the digestion significantly influences the magnitude of MPS [42]. For example, free EAAs are rapidly absorbed, which leads to higher peak concentrations of plasma EAAs and greater stimulation of MPS compared to casein, whey, or ground beef [38,39,43].…”
Section: Role Of Plasma Eaa Appearance Rate On Stimulation Of Mpsmentioning
confidence: 99%
“…Katsanos et al found that older adults, unlike young subjects, had limited responsiveness of MPS to a composition of dietary EAAs containing 26% of leucine, which is overcome by increasing the leucine content to 41% [31]. Additionally, although not an EAA, specific NEAAs such as arginine and citrulline can augment the MPS response to EAA supplementation [41] through various mechanisms, including improvement in muscle blood flow due to stimulation of nitric oxide production [51]. For example, arginine is the direct precursor of nitric oxide, a potent vasodilator, and its bioavailability in the blood is more effectively increased when citrulline is consumed compared to isonitrogenous arginine due to extensive consumption of arginine by the liver.…”
Section: Compositionmentioning
confidence: 99%